Reproductive Toxicity and Recovery Associated With 4-Non-ylphenol Exposure in Juvenile African Catfish (Clarias garepinus) - Sayed, Alaa El-Din H.; Eid, Zainab; Mahmoud, Usama M.; Lee, Jae-Seong; Mekkawy, Imam A. A. (Frontiers in Physiology, 2022)
Although, the 4-NP effects on fish’s reproductive hormones was assessed in several studies using adults’ models; however, the effect of this endocrine disruptor on immature fish’s reproductive hormones was not addressed commonly. This study aimed to study the reproductive toxicity and recovery associated with 4-nonylphenol exposure in juvenile African catfish (Clarias garepinus) using some hormones (17β-estradiol (E2), Testosterone (T), follicle stimulating hormone (FSH) and luteinizing hormone (LH)) and gonads histology as biomarkers. Toxic effects of 4-nonylphenol (4-NP) has been studied in many anmails models but still there is limited knowledge about the dose-dependent damage caused by 4-NP exposure in juvenile Clarias gariepinus. Healthy juvenile C. gariepinus categorized into four groups (n=3/ group; three replicates in each group). The first group was the control, and the other three groups were subjected to 4-NP concentrations as 0.1 mg/L, 0.2 mg/L, and 0.3 mg/L, respectively for 15 days, then were left for a recovery period of another 15 days. The reproductive hormones of C. gariepinus exposed to 4-NP for 15 days exhibited significant variations between treatments and the control (P < 0.05) were evident in E2 and T values, whereas FSH, LH, total protein and lipid peroxidation values showed non-significant difference among all groups. Such situation referred to the fact that the 15-day recovery period was insufficient to remove the impacts of 4-NP doses in concern. The trend of dose-dependent increase/decrease was recorded for T, E2, FSH, and LH. The histopathological alterations of 4-NP-treated in gonads tissues were recorded in juvenile of C. gariepinus reflecting their sensitivity to 4-NP-estrogenic like effects. Overall, our results investigate that recovery has improved the reproductive toxicity caused by 4-nonylphenol in juvenile of C. garepinus. Significant variations between the treated groups and the control group (P < 0.05) were evident in all parameters except for the Hb, MCV, MCH and MCHC. The parameters exhibiting significance decreased with such increased doses. Apoptotic frequency in erythrocytes and brain cells increased significantly with increased 4-NP exposure, indicating that 4-NP caused cytotoxic effects, such as apoptosis in a dose-dependent manner. However, these cellular alterations greatly decreased after the 15-day recovery period.